Ethnocentrism as a research object: a bibliometric approach - Botello-Juárez, Fernando Alonso; Vega-Almeida, Rosa Lidia; Arencibia-Jorge, Ricardo (Iberoamerican Journal of Science Measurement and Communication, 2024)
Objective. To characterize the world's scientific production on ethnocentrism and describe the evolution of its research lines over the last 80 years. Design/Methodology/Approach. Web of Science was used as a data source. Articles related to the study of ethnocentrism were analyzed using bibliometric methods, such as Bradford's Law and bibliographic coupling. A bibliographic review was also developed to describe the main research fronts identified. Results/Discussion. An exponential growth of literature was observed, as well as the absence of specialized journals on the subject, and a gradual increase of disciplines studying ethnocentrism, which shows a research activity in process of expansion and consolidation. Three main research fronts were identified and described, focused on the study of the personality of ethnocentric individuals, their group attitudes, and their behavior as consumers of products and services. Conclusions. The study provided a comprehensive overview of the current state of research on ethnocentrism, its evolution and significance in various historical and disciplinary contexts. The absence of solid library research on this topic provides opportunities for future studies on ethnocentric biases in bibliographic collections, user education, and classification systems. Originality/Value. To our knowledge, this is the first bibliometric study that analyzes the evolution of research on ethnocentrism in a global way. It also constitutes a first approach to the study of ethnocentrism in the field of Library and Information Science.